Prevalence of Hyperprolactinemia in Patients Undergoing Long-Term Proton Pump Inhibitor Therapy: Hyperprolactinemia in Patients Having Long-Term Proton Pump Inhibitor Therapy - Zubair, Muhammad; Amil, Javaria; Noureen, Sadia; Ikram Ul Haq, Muhammad; Azmat, Saddiqa; Majeed, Sadia (Pakistan Journal of Health Sciences, 2024)
Proton pump inhibitors used to treat gastrointestinal disorders cause various threatening effects and lead to an increase in serum prolactin levels. Objectives: To evaluate serum prolactin and macroprolactin levels in long-term proton pump inhibitor therapy patients. Method: An observational cross-sectional study was done between February 2023 and June 2024, at Niazi Welfare Foundation Teaching Hospital, Sargodha after approval from the institutional review board. Patients of either gender using proton pump inhibitors for ≥3 months, alone or in combination with histamine 2 receptor antagonists or pro-kinetics were included to measure serum prolactin levels. A duration of >3 months was taken as long-term therapy to see the impact on prolactin levels. The data were analyzed using SPSS version 25.0. Results: Out of the 166 patients, 102 (61.4%) were female, and 64 (38.6%) were male. The patient’s mean age was 42.6 ± 14.3 years, and serum prolactin level was 23.2ng/mL. Among the participants, 97 (58.4%) had normoprolactinemia, while 69 (41.6%) had hyperprolactinemia. A significant increase in hyperprolactinemia with longer proton pump inhibitor treatment duration was revealed. Conclusions: It was concluded that prolonged use of proton pump inhibitors has the potential to raise serum prolactin levels, highlighting the importance of thorough evaluation for optimal clinical management.